Introducción al sistema de gestión de mantenimiento productivo total para empresa de movimiento de suelos - Matejcic, Fabrizio (Universidad Nacional de Córdoba. Facultad de Ciencias Exactas, Físicas y Naturales. Escuela de Ingeniería Industrial., 2025)
This work aims to apply maintenance management for the family company "Matejcic Hermanos SH," which is in charge of offering services for the execution of civil works with road construction equipment, to make a contribution from the perspective of methods to the central workshop of this construction company. Currently, the company has 8 machineries (bulldozers, motor graders, backhoes, trucks, among others) and other equipment and tools to carry out its tasks.